ANALISIS FUNGSI EKSTRAKURIKULER SEPAK BOLA DI SMA TAMAN MULIA KABUPATEN KUBU RAYA - Istiqa Nurtiarani; Rustiyarso Rustiyarso; Supriyadi Supriyadi (Universitas Tanjungpura, 2020)
AbstractThis research aimed to discover about Analysis of the Extracurricular function of soccer in SMA Taman Mulia Kubu Raya Regency. The problem in this research is “How the extracurricular function of soccer in SMA Taman Mulia Kubu Raya Regency?”. Based of the problem then presened to subs problem that is how does the development function in the exreacurricular activities of soccer in SMA Taman Mulia Kubu Raya Regency, how does the social function in the exreacurricular activities of soccer in SMA Taman Mulia Kubu Raya Regency, how does the recretional function in the exreacurricular activities of soccer in SMA Taman Mulia Kubu Raya Regency. This research used a qualitative approach with descriptive method. This research used a qualitative approach with descriptive method. Techniques which are used are observation, interview, and documentation study. The analysis is presented descriptively qualitativeby using informants as much 8 people consisting of a representative of a students of school, a counselor of extracurricular soccer activities and 6 students who joined activities extracurricular soccer. The result of this study indicate that the function extracurricular activities of soccer in SMA Taman Mulia Kubu Raya Regency is good, because the development function that has been a good journey because students are able to develop creativity and talent. Social function proved good because the students were able to develop the ability and sense of responsinility.the recreational function proved to be good because the students showed a relaxed, happy and exhilarating feeling while following the extracurricular activities of soccer. Keywords::Extracurricular, Function,Senior High School Students, Soccer